Предмет: Алгебра,
автор: vikki1980timo
5 - 5х = 2.5 (2х - 1) -2
Ответ с решением, очень срочно пожалуйста!!!
Ответы
Автор ответа:
2
5- 5х = 2,5(2х-1)-2
5-5х = 5х - 2,5 - 2
5 - 5х = 5х -4,5
5+4,5=10х
9,5=10х
10х=9,5
Х=0,95
5-5х = 5х - 2,5 - 2
5 - 5х = 5х -4,5
5+4,5=10х
9,5=10х
10х=9,5
Х=0,95
vikki1980timo:
Спасибо ♡
Автор ответа:
2
5-5х=2,5(2х-1)-2
5-5х=5х-2,5-2
-5х-5х=-2,5-2-5
-10х=-9,5х
х=0,95
5-5х=5х-2,5-2
-5х-5х=-2,5-2-5
-10х=-9,5х
х=0,95
Похожие вопросы
Предмет: Русский язык,
автор: никитис
Предмет: Английский язык,
автор: ArtemAlimkhano
Предмет: Русский язык,
автор: Ralli12345
Предмет: Химия,
автор: lenanorko5505
Предмет: Математика,
автор: мелисса28